Prediction of creep crack initiation behaviour in 316H stainless steel using stress dependent creep ductility. (15th October 2016) - Quintero, Hanna; Mehmanparast, Ali
Highlights: The creep crack initiation behaviour in five specimen geometries has been predicted by FE simulations. A stress dependent creep ductility model is employed in creep damage calculations. The FE results have shown that the creep crack initiation behaviour of the material is sensitive to the specimen geometry and applied load level. FE simulations have shown that the highest and lowest creep crack initiation trends were found in M(T) and CS(T) specimen geometry, respectively. The creep crack initiation transition behaviour from short-term to long-term trends has been predicted to occur within the range of 1 × 10 − 7 < C * < 2 × 10 − 6 MPam/h. Abstract: The creep crack initiation behaviour of Type 316H stainless steel at 550 °C has been predicted by implementing a stress dependent creep ductility and average creep strain rate model in finite element analyses. Simulations were performed on five specimen geometries: C(T), CS(T), DEN(T), M(T) and SEN(T). The predicted results have been characterised using the C * fracture mechanics parameter and the short-term, long-term and transition creep crack initiation trends are predicted for each of the specimen geometries examined. The prediction results have been validated through comparison with experimental data available in the literature. The predicted short-term and long-term creep crack initiation trends have also been compared with NSW prediction lines. The predicted results, from each specimen geometry, are compared to each other and the differences in crack initiation trends have been discussed in terms of the specimen geometry, in-plane constraint and stress level effects on the creep crack initiation behaviour of the material. A mesh sensitivity analysis has also been performed to find the optimum mesh size for performing crack initiation simulations. Graphical abstract: